Star formation and quenching in galaxy formation models - Asquith, Rachel (2019)
Galaxies locally have been observed to have a bimodal distribution for many properties, such as colour, star formation rate and morphology. These properties can be used to separate galaxies into two classes - the 'blue cloud' and the 'red sequence'. Galaxies move from the blue cloud to the red sequence in a process called 'quenching'. Learning exactly how and why galaxies are quenched is vital to understanding galaxy evolution. In this thesis, we use galaxy formation models to investigate the processes governing star formation and quenching, with the aim of understanding exactly which mechanisms are needed to produce a realistic population of galaxies.